Identifying the factors affecting individual resistance against organizational change - VAYVAY, ÖZALP (My University, 2023)
This study aims to determine the factors affecting individual resistance. Literature review shows that job insecurity, emotional distress, and identity division are potential variables that will affect individual resistance. As a result of the factor and reliability analysis, the emotional distress scale consisted of 3 sub-factors: excitement, anxiety, and enthusiasm. Individual resistance, job insecurity, and identity fragmentation scales emerged as the only factors. As a result of simple and multiple regression analyses, it is seen that all independent variables significantly affect individual resistance. Job Insecurity has a significant and positive effect on individual resistance. It is seen that anxiety has a significant and negative effect on individual resistance, and enthusiasm has a significant and positive effect. The identity division has a significant and positive effect on individual resistance. Anxiety and enthusiasm variables, which are the sub-dimensions of emotional distress, are the variables that most affect individual resistance. In order to encounter less resistance and problems in the change process, employees need to be trained and prepared for a change in advance. Organizational change can only be achieved with the participation and support of employees. The study concludes with recommendations for managers at the strategy, operations, and human resources management levels.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Siyaset Bilimi; Kamu Yönetimi; İşletme; Eğitim; Social Sciences and Humanities; Sociology; Political Science; Public Administration; Management; Education; Sosyal Bilimler (SOC); Ekonomi ve İş; Sosyal Bilimler Genel; İŞLETME; EĞİTİM VE EĞİTİM ARAŞTIRMASI; KAMU YÖNETİMİ; SOSYAL BİLİMLER, İNTERDİSİPLİNER; Social Sciences (SOC); ECONOMICS & BUSINESS; SOCIAL SCIENCES, GENERAL; BUSINESS; EDUCATION & EDUCATIONAL RESEARCH; PUBLIC ADMINISTRATION; SOCIAL SCIENCES, INTERDISCIPLINARY; Sosyal Bilimler ve Beşeri Bilimler; Sosyal Bilimler (çeşitli); Strateji ve Yönetim; Social Sciences & Humanities; Social Sciences (miscellaneous); Strategy and Management; Emotional Distress; Identity Division; Individual Resistance; Job Insecurity; Organizational Change; Individual Resistance; Job Insecurity; Emotional Distress; Identity Division; Organizational Change